The impact of different views of theories of language development on language learning - Jalaluddin, Ilyana; Abdullah, Muhammad Abubakar (Anfo Publication House, 2021)
Within the middle of the 20th century, three main theoretical positions have been developed to explain language development in children. The major assumptions are advanced by the behaviorists’ innatists’ as well as interactionists’ schools. This paper explores the impacts of their different views on the subject. The views of each theory and its impact on language learning have been clearly stated and examined with a view to assessing their individual contributions and strength. The study argued that a combined treatment of the three views would yield much better results in teaching and learning process.